Direct oral anticoagulant plasma levels' striking increase in severe COVID‐19 respiratory syndrome patients treated with antiviral agents: The Cremona experience. (6th May 2020) - Testa, Sophie; Prandoni, Paolo; Paoletti, Oriana; Morandini, Rossella; Tala, Maurizio; Dellanoce, Claudia; Giorgi‐Pierfranceschi, Matteo; Betti, Monia; Danzi, Gian Battista; Pan, Angelo; Palareti, Gualtiero
Abstract: Background: Antiviral drugs are administered in patients with severe COVID‐19 respiratory syndrome, including those treated with direct oral anticoagulants (DOACs). Concomitant administration of antiviral agents has the potential to increase their plasma concentration. A series of patients managed in the Cremona Thrombosis Center were admitted at Cremona Hospital for SARS‐CoV‐2 and started antiviral drugs without stopping DOAC therapy. DOAC plasma levels were measured in hospital and results compared with those recorded before hospitalization. Methods: All consecutive patients on DOACs were candidates for administration of antiviral agents (lopinavir, ritonavir, or darunavir). Plasma samples for DOAC measurement were collected 2to 4 days after starting antiviral treatment, at 12 hours from the last dose intake in patients on dabigatran and apixaban, and at 24 hours in those on rivaroxaban and edoxaban. For each patient, C‐trough DOAC level, expressed as ng/mL, was compared with the one measured before hospitalization. Results: Of the 1039 patients hospitalized between February 22 and March 15, 2020 with COVID‐19 pneumonia and candidates for antiviral therapy, 32 were on treatment with a DOAC. DOAC was stopped in 20 and continued in the remaining 12. On average, C‐trough levels were 6.14 times higher during hospitalization than in the pre‐hospitalization period. Conclusion: DOAC patients treated with antiviral drugs show an alarming increase in DOAC plasma levels. In order to prevent bleeding complications, we believe that physicians should consider withholding DOACs from patients with SARS‐CoV‐2 and replacing them with alternative parenteral antithrombotic strategies for as long as antiviral agents are deemed necessary and until discharge.